Play Turned Painful: A Teenager’s Tibial Pilon Fracture from A Simple Jump - Victoria M Koniuk; Brody M Fogleman; Lindsay Tjiattas-Saleski (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: An 18-year-old male presented with severe left ankle pain and inability to bear weight after jumping from a three-foot platform. Physical examination revealed decreased range of motion of the left ankle without visible deformity or neurovascular deficits. Imaging studies showed a vertical fracture of the distal tibia—a pilon fracture without fibular involvement. Discussion: Pilon fractures involve the distal tibial articular surface and are rare. They typically result from high-energy trauma and often involve the fibula. This case illustrates a low-energy mechanism resulting in a pilon fracture without fibular involvement in a young patient without typical risk factors. It highlights the importance of considering pilon fractures in low-energy ankle injuries and the need for appropriate management even in less-complex cases.